Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To simplify the given expression
[tex]\[ \frac{x^2-12 x+32}{2 x^3-18 x^2+40 x} \cdot \frac{x^2-1}{x^2-7 x-8} \div \frac{x^2+4 x-5}{25-x^2} \][/tex]
we will proceed step-by-step, first by simplifying each component individually and then combining the results.
### Step 1: Simplify each individual fraction
1. Simplify [tex]\(\frac{x^2-12x+32}{2x^3-18x^2+40x}\)[/tex]
- Factor the numerator: [tex]\(x^2 - 12x + 32 = (x - 4)(x - 8)\)[/tex]
- Factor the denominator: [tex]\(2x^3 - 18x^2 + 40x = 2x(x^2 - 9x + 20) = 2x(x-4)(x-5)\)[/tex]
- Simplified form: [tex]\(\frac{(x-4)(x-8)}{2x(x-4)(x-5)} = \frac{x-8}{2x(x-5)}\)[/tex] (Cancel out [tex]\(x-4\)[/tex])
2. Simplify [tex]\(\frac{x^2-1}{x^2-7x-8}\)[/tex]
- Factor the numerator: [tex]\(x^2 - 1 = (x-1)(x+1)\)[/tex]
- Factor the denominator: [tex]\(x^2 - 7x - 8 = (x-8)(x+1)\)[/tex]
- Simplified form: [tex]\(\frac{(x-1)(x+1)}{(x-8)(x+1)} = \frac{x-1}{x-8}\)[/tex] (Cancel out [tex]\(x+1\)[/tex])
3. Simplify [tex]\(\frac{x^2+4x-5}{25-x^2}\)[/tex]
- Factor the numerator: [tex]\(x^2 + 4x - 5 = (x+5)(x-1)\)[/tex]
- Factor the denominator: [tex]\(25 - x^2 = (5-x)(5+x) = -(x-5)(x+5)\)[/tex]
- Simplified form: [tex]\(\frac{(x+5)(x-1)}{-(x-5)(x+5)} = \frac{x-1}{-(x-5)} = -\frac{x-1}{x-5}\)[/tex] (Cancel out [tex]\(x+5\)[/tex])
### Step 2: Combine the simplified components
Substitute the simplified forms into the original expression:
[tex]\[ \frac{x-8}{2x(x-5)} \cdot \frac{x-1}{x-8} \div \left(-\frac{x-1}{x-5}\right) \][/tex]
### Step 3: Perform the operations
1. Multiply the first two fractions:
[tex]\[ \frac{x-8}{2x(x-5)} \cdot \frac{x-1}{x-8} = \frac{(x-8)(x-1)}{2x(x-5)(x-8)} = \frac{x-1}{2x(x-5)} \quad \text{(Cancel out \(x-8\))} \][/tex]
2. Dividing by a fraction is equivalent to multiplying by its reciprocal:
[tex]\[ \frac{x-1}{2x(x-5)} \div \left(-\frac{x-1}{x-5}\right) = \frac{x-1}{2x(x-5)} \cdot \frac{x-5}{-(x-1)} = \frac{(x-1)(x-5)}{2x(x-5)} \cdot \frac{1}{-(x-1)} = \frac{1}{2x} \cdot \frac{1}{-1} = -\frac{1}{2x} \][/tex]
### Final Simplification:
Therefore, the fully simplified form of the given expression is:
[tex]\[ -\frac{1}{2x} \][/tex]
The final simplified result is:
[tex]\[ -\frac{1}{2x} \][/tex]
[tex]\[ \frac{x^2-12 x+32}{2 x^3-18 x^2+40 x} \cdot \frac{x^2-1}{x^2-7 x-8} \div \frac{x^2+4 x-5}{25-x^2} \][/tex]
we will proceed step-by-step, first by simplifying each component individually and then combining the results.
### Step 1: Simplify each individual fraction
1. Simplify [tex]\(\frac{x^2-12x+32}{2x^3-18x^2+40x}\)[/tex]
- Factor the numerator: [tex]\(x^2 - 12x + 32 = (x - 4)(x - 8)\)[/tex]
- Factor the denominator: [tex]\(2x^3 - 18x^2 + 40x = 2x(x^2 - 9x + 20) = 2x(x-4)(x-5)\)[/tex]
- Simplified form: [tex]\(\frac{(x-4)(x-8)}{2x(x-4)(x-5)} = \frac{x-8}{2x(x-5)}\)[/tex] (Cancel out [tex]\(x-4\)[/tex])
2. Simplify [tex]\(\frac{x^2-1}{x^2-7x-8}\)[/tex]
- Factor the numerator: [tex]\(x^2 - 1 = (x-1)(x+1)\)[/tex]
- Factor the denominator: [tex]\(x^2 - 7x - 8 = (x-8)(x+1)\)[/tex]
- Simplified form: [tex]\(\frac{(x-1)(x+1)}{(x-8)(x+1)} = \frac{x-1}{x-8}\)[/tex] (Cancel out [tex]\(x+1\)[/tex])
3. Simplify [tex]\(\frac{x^2+4x-5}{25-x^2}\)[/tex]
- Factor the numerator: [tex]\(x^2 + 4x - 5 = (x+5)(x-1)\)[/tex]
- Factor the denominator: [tex]\(25 - x^2 = (5-x)(5+x) = -(x-5)(x+5)\)[/tex]
- Simplified form: [tex]\(\frac{(x+5)(x-1)}{-(x-5)(x+5)} = \frac{x-1}{-(x-5)} = -\frac{x-1}{x-5}\)[/tex] (Cancel out [tex]\(x+5\)[/tex])
### Step 2: Combine the simplified components
Substitute the simplified forms into the original expression:
[tex]\[ \frac{x-8}{2x(x-5)} \cdot \frac{x-1}{x-8} \div \left(-\frac{x-1}{x-5}\right) \][/tex]
### Step 3: Perform the operations
1. Multiply the first two fractions:
[tex]\[ \frac{x-8}{2x(x-5)} \cdot \frac{x-1}{x-8} = \frac{(x-8)(x-1)}{2x(x-5)(x-8)} = \frac{x-1}{2x(x-5)} \quad \text{(Cancel out \(x-8\))} \][/tex]
2. Dividing by a fraction is equivalent to multiplying by its reciprocal:
[tex]\[ \frac{x-1}{2x(x-5)} \div \left(-\frac{x-1}{x-5}\right) = \frac{x-1}{2x(x-5)} \cdot \frac{x-5}{-(x-1)} = \frac{(x-1)(x-5)}{2x(x-5)} \cdot \frac{1}{-(x-1)} = \frac{1}{2x} \cdot \frac{1}{-1} = -\frac{1}{2x} \][/tex]
### Final Simplification:
Therefore, the fully simplified form of the given expression is:
[tex]\[ -\frac{1}{2x} \][/tex]
The final simplified result is:
[tex]\[ -\frac{1}{2x} \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.